Horses, Girls, and Agency: Gender in Play Pedagogy - Rainio, Anna Pauliina (Outlines. Critical Practice Studies, 2009)
This is a study of the development of student agency from a gender perspective in a Finnish classroom. The data originates from an ethnographic research project in an elementary school classroom engaging in a play pedagogy project called a “playworld.” The article has two purposes. The first is to examine the potential of imagination and improvised fantasy play in the development of agency. The second is to investigate the role of gender as a social category in shaping the students’ possibilities for agency in the play pedagogical setting. The creative use of imagination is at the center of the playworld pedagogy. However, it has rarely been studied in relation to the potentially uneven or stereotypic consequences of cultural tools, symbols, and categories. The analytical focus is on the gender-related categorization of a ‘horse girl’ and the role it played in the development of the agency of two seven-year-old girls as they participated in the playworld. I have used a multidisciplinary analytical framework to sensitize myself to the data. In the article I combine Vygotsky’s ideas of double stimulation, Sacks’ categorization analysis and, Holzkamp’s concept of action potence. The results show that the playworld pedagogy that explicitly aimed at developing children’s agency and collaboration was strongly gender categorized and thus was constraining for the girls in this study. On the other hand, the girls’ unplanned fantasy play, which took place on the sidelines of the classroom activity, contained important agentive elements. It gave the girls a sense of agency crucial to their enactment of agency in the wider playworld setting. It is argued that the girls were able to become agentive players in the activity through questioning the gendered categories openly in the classroom.